2021
DOI: 10.1089/dna.2020.5823
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of UBE2T Predicting Poor Survival of Epithelial Ovarian Cancer: Based on Comprehensive Analysis of UBE2s, Clinical Samples, and the GEO Database

Abstract: Background Ubiquitin-conjugating enzymes E2 (UBE2) have been reported in the microenvironment of various malignant tumors, but their correlation with ovarian cancer remains elusive.Methods: The Oncomine, GEPIA, Kaplan-Meier Plotter, cBioPortal, and STRING databases were used to systematically analyze the expression pattern, prognostic value, genetic variation, and biological function of 12 members of the UBE2 gene family in ovarian cancer. UBE2T exhibited a strong correlation with ovarian cancer and was thus f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Ubiquitin-conjugating enzyme E2A (UBE2A), which contains a 456-bp open reading frame, was predicted as a downstream target of miR-527 using bioinformatics tools, luciferase activity assays, qRT-PCR, and western blotting. It has been reported that increased UBE2A expression predicts poor survival in patients with ovarian cancer [ 44 ]. In addition, an RNA-seq signature involving UBE2A can predict the prognosis of multiple myeloma (MM) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-conjugating enzyme E2A (UBE2A), which contains a 456-bp open reading frame, was predicted as a downstream target of miR-527 using bioinformatics tools, luciferase activity assays, qRT-PCR, and western blotting. It has been reported that increased UBE2A expression predicts poor survival in patients with ovarian cancer [ 44 ]. In addition, an RNA-seq signature involving UBE2A can predict the prognosis of multiple myeloma (MM) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…UBE2T (also known as FANCT ) expression appears to be a genetic marker distinguishing LMP from HGSOC ( Table 2 ). It has been reported that increased expression of UBE2T is associated with poor survival in EOC [ 12 ]. Machida et al (2006) identified UBE2T as a ubiquitin conjugase essential in the Fanconi anemia pathway (also known as the Fanconi anemia/BRCA pathway) and as a protein that is important in protecting chromosome stability [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…UBE2T has now been well characterized as a gene coding for a ubiquitin conjugase involved in the DNA damage response associated with the Fanconi anemia (FA) pathway [ 13 , 14 ]. UBE2T overexpression is associated with several cancers including prostate cancer [ 15 ], gastric cancer, [ 16 ], breast cancer [ 17 ], EOC [ 12 ], and multiple myeloma [ 18 ]. The role of UBE2T as an E2 conjugase in the FA pathway is to transfer ubiquitin from UBE2T to the E3 ligase FANCL, which, in turn, ubiquitinates FANCD2 ( Figure 2 ) [ 13 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interest in nding useful biomarkers for diagnosis and treatment of breast cancer has been accumulating. Increasing data indicated that aberrant UBE2T expression has serve important roles in almost all cell biological behaviors, including growth, cell cycle, apoptosis, differentiation, apoptosis and metastasis (14)(15)(16)(17). However, little is known about the function of UBE2T in breast cancer.…”
Section: Discussionmentioning
confidence: 99%